1980
DOI: 10.1042/bj1860791
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effects on the formation of dolichyl monophosphate mannose by microsomal preparations of rat adipose tissue

Abstract: Microsomal preparations from rat adipose tissue catalyse the transfer of [(14)C]mannose from GDP-[(14)C]mannose to an endogenous acceptor forming a [(14)C]mannosyl lipid. The mannosyl lipid co-chromatographs with hen oviduct dolichyl monophosphate beta-mannose on three solvent systems. It is stable to mild alkaline hydrolysis, but strong alkaline treatment yields a compound that co-migrates with mannose 1-phosphate. The mannosyl lipid is labile to mild acid hydrolysis, yielding [(14)C]mannose. Formation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…more recently, a similar effect on tracheal galactosylation was described [17]. The discovery of the dolichol pathway of the glycoprotein mannosylation gave rise to sev eral works dealing with the adaptation of this compound to various diets, either in the liver [18,19], the adipose tissue [13] or the pan creas [3. 4], In a previous paper [5], we described large variations of intestinal glycosyltransferase activities, which do not in volve dolichol intermediates, to nutritional factors: activation of fucosyltransferase ac tivity by a high-protein diet and inhibition by a high-fat diet.…”
Section: Introductionmentioning
confidence: 99%
“…more recently, a similar effect on tracheal galactosylation was described [17]. The discovery of the dolichol pathway of the glycoprotein mannosylation gave rise to sev eral works dealing with the adaptation of this compound to various diets, either in the liver [18,19], the adipose tissue [13] or the pan creas [3. 4], In a previous paper [5], we described large variations of intestinal glycosyltransferase activities, which do not in volve dolichol intermediates, to nutritional factors: activation of fucosyltransferase ac tivity by a high-protein diet and inhibition by a high-fat diet.…”
Section: Introductionmentioning
confidence: 99%
“…It is of interest that supplementary ubiquinone protects against adriamycin-induced cardiomyopathy (Kishi et al, 1976), perhaps by compensating for diminished synthesis, although there may also be interference with ubiquinone function (Folkers et al, 1977) because of the structural relationship between the benzoquinone ring of ubiquinone and the tautomeric quinone and quinol rings of adriamycin. Dolichol Lucas et al (1980) showed that dietary cholesterol increased dolichyl monophosphate concentration in rat adipose tissue and this response was associated with an increased transfer of mannose into mannosyl lipids. Tavares et al (1981) found that 1% (w/w) dietary cholesterol also increased the dolichol content of rat liver and stimulated the incorporation of mevalonate into dolichol and dolichyl diphosphate oligosaccharide with an associated enhancement of protein N-glycosylation.…”
Section: Ubiquinonementioning
confidence: 99%
“…Hu man liver mannosyltransferase is similar to comparable enzymes studied from several sources including Acanthamoeba castellami [4], yeast [11,12], pig aorta [13], rat liver [3,14] and rat adipose tissue [9] in that small concentrations (2.5-20 ml) of divalent cat ion (Mn+2, Mg+2, Co+2, Ca+2) are required for, or stimulate, activity. Mn+2 has usually given best activity although Mg+2 [11] and Co+2 [9] have been found to be optimal in some cases. A second mannosyltransferase has been described in rabbit liver [15] and pig aorta [16] which appears to be different from the human liver enzyme (and most of the …”
Section: Preliminary Product Characterizationmentioning
confidence: 99%
“…Portions of the extracted products were subjected to acid or base hydrolysis after the modified procedure of Lucas et al [9], Acid hydrolysis was carried out at 50 and 80 °C for 2 h using 0.2 and 0.5 MHC1 in 50% (v/v) 17-propanol, and base hydrolysis was carried out at 60 "C for 30 and 60 min using 0.05 M NaOH in 90% (v/v) ethanol. The acid and base hydrolysates, creases in activity are seen with increasing amounts of substrate from 33,000 to 400.000 dpm/assay ( fig.…”
Section: Enzymatic Assaysmentioning
confidence: 99%